Medical Imaging 2018: Imaging Informatics for Healthcare, Research, and Applications 2018
DOI: 10.1117/12.2292563
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing lung nodules detection and annotation

Abstract: We present crowdsourcing as an additional modality to aid radiologists in the diagnosis of lung cancer from clinical chest computed tomography (CT) scans. More specifically, a complete workflow is introduced which can help maximize the sensitivity of lung nodule detection by utilizing the collective intelligence of the crowd. We combine the concept of overlapping thin-slab maximum intensity projections (TS-MIPs) and cine viewing to render short videos that can be outsourced as an annotation task to the crowd. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In the literature, experiences with crowdsourcing medical imaging tasks to untrained persons in the community-at-large have been described with variable success. Such tasks include annotations of airways, lung nodules, kidney and liver segmentations, and colon polyp classification on CT colonography images [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, experiences with crowdsourcing medical imaging tasks to untrained persons in the community-at-large have been described with variable success. Such tasks include annotations of airways, lung nodules, kidney and liver segmentations, and colon polyp classification on CT colonography images [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Classify (Albarqouni et al, 2016a), (Brady et al, 2014), (Brady et al, 2017), , (dos Reis et al, 2015), (Eickhoff, 2014), (Foncubierta Rodríguez and Müller, 2012), (Gur et al, 2017), (de Herrera et al, 2014), (Holst et al, 2015), (Huang and Hamarneh, 2017), (Keshavan et al, 2018), (Lawson et al, 2017), (Malpani et al, 2015), (Mavandadi et al, 2012, (Mitry et al, 2013), (Mitry et al, 2015), (Nguyen et al, 2012), (Park et al, 2016), (Park et al, 2017), (Smittenaar et al, 2018), (Sonabend et al, 2017), (Sullivan et al, 2018) Segment (Roethlingshoefer et al, 2017), (Boorboor et al, 2018), (Bruggemann et al, 2018), (Cabrera-Bean et al, 2017), (Chávez-Aragón et al, 2013), (Cheplygina et al, 2016), (Ganz et al, 2017), (Gurari et al, 2015b), (Heller et al, 2017), (Irshad et al, 2015), (Lee and Tufail, 2014), (Lee et al, 2016), (Lejeune et al, 2017), (Luengo-Oroz et al, 2012), (Maier-Hein et al, 2014a), (Maier-Hein et al, 2016), (O'Neil et al, 2017), (Park et al, 2018),…”
Section: Task Papersmentioning
confidence: 99%
“…Click (Bruggemann et al, 2018), (Cabrera-Bean et al, 2017), (Della Mea et al, 2014), (Huang and Hamarneh, 2017), (Lawson et al, 2017), (Lejeune et al, 2017), (Luengo-Oroz et al, 2012), (Park et al, 2018), (Rajchl et al, 2016) Click + Compare (Maier-Hein et al, 2014b), (Maier-Hein et al, 2015), (Maier-Hein et al, 2016) Click + Draw (Irshad et al, 2015) Compare (Ørting et al, 2017) Draw (Roethlingshoefer et al, 2017), (Boorboor et al, 2018), (Chávez-Aragón et al, 2013), (Cheplygina et al, 2016), (Ganz et al, 2017), (Gurari et al, 2015b), (Heller et al, 2017), (Lee and Tufail, 2014), (Lee et al, 2016), (Maier-Hein et al, 2014a), (O'Neil et al, 2017), (Sameki et al, 2016), (Sharma et al, 2017) Rate (Albarqouni et al, 2016a), (Albarqouni et al, 2016b), (Brady et al, 2014), (Brady et al, 2017), , (dos Reis et al, 2015), (Eickhoff, 2014), (Foncubierta Rodríguez and Müller, 2012), (Gur et al, 2017), (de Herrera et al, 2014), (Holst et al, 2015), (Keshavan et al, 2018), (Mavandadi et al, 2012), (McKenna et al, 2012), (Mitry ...…”
Section: Interaction Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on crowdsourcing have shown promising results on biomedical images. For example, [21] applied crowdsourcing techniques for the detection of dividing cells in breast cancer histology images, while [22] used a crowdsourcing framework for lung nodule detection and annotation to aid radiologists in lung cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%